2012
DOI: 10.1096/fj.12-220657
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding the oligomeric state: αB‐crystallin inhibits fragmentation and induces dissociation of apolipoprotein C‐II amyloid fibrils

Abstract: The in vivo aggregation of proteins into amyloid fibrils suggests that cellular mechanisms that normally prevent or reverse this aggregation have failed. The small heat-shock molecular chaperone protein αB-crystallin (αB-c) inhibits amyloid formation and colocalizes with amyloid plaques; however, the physiological reason for this localization remains unexplored. Here, using apolipoprotein C-II (apoC-II) as a model fibril-forming system, we show that αB-c binds directly to mature amyloid fibrils (Kd 5.4 ± 0.5 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 40 publications
7
58
0
Order By: Relevance
“…Recently, it has been demonstrated that, even when present at very low concentrations, molecular chaperones may inhibit the cytotoxicity of preformed misfolded oligomers formed by A, IAPP and HypF-N and fibrils formed by apolipoprotein C-II, by binding to them and converting them into larger aggregates (Ojha et al, 2011;Mannini et al, 2012, Binger et al, 2013. Interestingly, this chaperone-induced effect has been found to occur in the absence of any major structural reorganisation within the individual oligomers, which appear to maintain their overall structure and just assemble into larger species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been demonstrated that, even when present at very low concentrations, molecular chaperones may inhibit the cytotoxicity of preformed misfolded oligomers formed by A, IAPP and HypF-N and fibrils formed by apolipoprotein C-II, by binding to them and converting them into larger aggregates (Ojha et al, 2011;Mannini et al, 2012, Binger et al, 2013. Interestingly, this chaperone-induced effect has been found to occur in the absence of any major structural reorganisation within the individual oligomers, which appear to maintain their overall structure and just assemble into larger species.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these functions, chaperones have recently been found to suppress in vitro the toxic effects of protein aggregates after the aggregates have formed (Ojha et al, 2011;Mannini et al, 2012;Cascella et al, 2013a;Cascella et al, 2013b;Binger et al, 2013). In particular, it has been found for a range of systems that misfolded protein oligomers, incubated with sub-stoichiometric concentrations of chaperones in vitro, can be converted into large aggregates with substantially reduced toxicity, in the absence of any significant structural reorganisation of the individual molecules within the aggregates (Mannini et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the design of such studies does not address the effect(s) sHsps have on the latter stages of aggregation, which is as important to consider since, in vivo, levels of sHsps in the cell increase after aggregation has commenced as a result of the activation of the stress response [104,105]. Apart from interacting with monomeric species, sHsps also bind to species formed further along the aggregation pathway, including mature amyloid fibrils [106][107][108][109]. For example, when introduced during the elongation phase of α-synuclein (α-syn) or amyloid- peptide (A aggregation, αBc prevents further fibril growth by binding along the length of mature fibrils, preventing secondary nucleation events that facilitate further fibril growth [106][107][108].…”
Section: The Chaperone Mechanism Of Shspsmentioning
confidence: 99%
“…For example, when introduced during the elongation phase of α-synuclein (α-syn) or amyloid- peptide (A aggregation, αBc prevents further fibril growth by binding along the length of mature fibrils, preventing secondary nucleation events that facilitate further fibril growth [106][107][108]. Our recent work, using apolipoprotein C-II (apoC-II) as a model fibril-forming protein, has shown that, by binding to fibrils, αBc stabilises them, preventing their (dilution-induced) fragmentation, and causes them to associate (tangle) into larger species reminiscent of protein inclusions [109]. Both fibril fragmentation and secondary nucleation can be the main sources of small oligomers thought to be responsible for the toxicity associated with the aggregation process [110].…”
Section: The Chaperone Mechanism Of Shspsmentioning
confidence: 99%